A New Root-Knot Nematode Parasitizing Sea Rocket from Spanish Mediterranean Coastal Dunes: Meloidogyne dunensis n. sp. (Nematoda: Meloidogynidae) - Palomares Rius, J. E. (The Society of Nematologists, 2007)
High infection rates of European sea rocket feeder roots by an unknown root-knot nematode were found in a coastal dune soil at Cullera (Valencia) in central eastern Spain. Morphometry, esterase and malate dehydrogenase electrophoretic phenotypes and phylogenetic trees demonstrated that this nematode species differs clearly from other previously described root-knot nematodes. Studies of host-parasite relationships showed a typical susceptible reaction in naturally infected European sea rocket plants and in artificially inoculated tomato (cv. Roma) and chickpea (cv. UC 27) plants. The species is herein described and illustrated and named as Meloidogyne dunensis n. sp. The new root-knot nematode can be distinguished from other Meloidogyne spp. by: (i) perineal pattern rounded-oval, formed of numerous fine dorsal and ventral cuticle striae and ridges, lateral fields clearly visible; (ii) female excretory pore at the level of stylet knobs, EP/ST ratio 1.6; (iii) second-stage juveniles with hemizonid located 1 to 2 annuli anteriorly to excretory pore and long, narrow, tapering tail; and (iv) males with lateral fields composed of four incisures anteriorly and posteriorly, while six distinct incisures are observed for large part at mid-body. Phylogenetic trees derived from distance and maximum parsimony analyses based on 18S, ITS1–5.8S-ITS2 and D2-D3 of 28S rDNA showed that M. dunensis n. sp. can be differentiated from all described root-knot nematode species, and it is clearly separated from other species with resemblance in morphology, such as M. duytsi, M. maritima, M. mayaguensis and M. minor.